IMPLIKASI SISTEM PENERIMAAN DAN PELATIHAN TERHADAP KEPUASAN KERJA PEGAWAI RSUD RA. BASOENI - RETNONINGSIH, WIWIK (Jurnal Pendidikan Administrasi Perkantoran (JPAP), 2013)
ABSTRACT   Recruitment and training systems that occurs will have implications to the employee’s job satisfaction. The last recruitment system in RA. Basoeni Hospital held in 2009, while the training system can not be directly implemented because it requires a submission to the Central Government first. This research is quantitative explanation research that aims to determine the condition of recruitment and training systems to the job satisfaction of RA. Basoeni hospital’s employees and the implication of  recruitment and training systems to the RA. Basoeni hospital’s employees either simultaneously or partially. This research uses saturation sampling that consists of 55 paramedic nurses as the respondents. The condition of recruitment and training systems to the job satisfaction of RA. Basoeni hospital’s employees categorized as very high, it means the recruitment and training systems to the job satisfaction of RA. Basoeni hospital’s employees is very good. While the implication of recruitment and training systems to the job satisfaction of RA. Basoeni hospital’s employees either partially or simultaneously are positive and significant.   Keywords: recruitment system, training system, job satisfaction